An alternative formulation for quasi-static frictional and cohesive contact problems - Areias, P. (2014)
It is known by Engineering practitioners that quasi-static contact problems with friction and cohesive laws often present convergence difficulties in Newton iteration. These are commonly attributed to the non-smoothness of the equilibrium system. However, non-uniqueness of solutions is often an obstacle for convergence. We discuss these condi- tions in detail and present a general algorithm for 3D which is shown to have quadratic convergence in the Newton–Raphson iteration even for parts of the domain where multiple solutions exist. Chen–Mangasarian replacement functions remove the non-smoothness corresponding to both the stick- slip and normal complementarity conditions. Contrasting with Augmented Lagrangian methods, second-order updat- ing is performed for all degrees-of-freedom. Stick condi- tion is automatically selected by the algorithm for regions with multiple solutions. The resulting Jacobian determinant is independent of the friction coefficient, at the expense of an increased number of nodal degrees-of-freedom. Aspects such as a dedicated pivoting for constrained problems are also of crucial importance for a successful solution finding. The resulting 3D mixed formulation, with 7 degrees-of-freedom in each node (displacement components, friction multiplier, friction force components and normal force) is tested with representative numerical examples (both contact with fric- tion and cohesive force), which show remarkable robustness and generality.